THE ANALYSIS OF ACTIVE LEARNING AND CRITICAL THINKING TO THE STUDENT’S PARTICIPATION IN ENGLISH DEBATE COMMUNITY - Sudiarna Ningsih; Erwin Akib; Wildhan Burhanuddin (Indonesian Journal of Psycholinguistics, 2022)
This research aims to know the The Analysis of Active Learning and Critical Thinking to the Students Participation in English Debate Community. The research methodology of this research is descriptive qualitative. The techniques of collecting data are speaking test used technique debate and interview test used google forms. The result of this research found that active learning and critical thinking have a connection to debate skills. They are related each other. The active learning may improve critical thinking ability, while debate skills can be improved by having a good critical thinking.